Heterogeneity of the Triassic Lacustrine Yanchang Shale in the Ordos Basin, China, and Its Implications for Hydrocarbon Primary Migration - Yuhong Lei; Likuan Zhang; Xiangzeng Wang; Naigui Liu; Ming Cheng; Zhenjia Cai; Jintao Yin (Applied Sciences, 2025)
The pathways and mechanisms of primary hydrocarbon migration, which are still not well understood, are of great significance for evaluating both conventional and unconventional oil and gas resources, understanding the mechanisms of shale oil retention, and predicting sweet spots. To investigate the petrography, geochemistry, and pore systems of organic-rich mudstones and organic-lean sand-silt intervals in core samples from the Yanchang shale in the Ordos Basin, China, we conducted thin-section observation, X-ray diffraction, Rock-Eval pyrolysis, field emission scanning electron microscopy (FE-SEM), and porosity analysis. Sand-silt intervals are heterogeneously developed within the Yanchang shale. The petrology, mineral composition, geochemistry, type, and content of solid organic matter as well as the pore type, pore size, and porosity of these intervals differ significantly from those of mudstones. Compared with mudstones, sand-silt intervals typically have coarser detrital grain sizes, higher contents of quartz, feldspar, and migrated solid bitumen (MSB), larger pore sizes, higher porosity, and higher oil saturation index (OSI). In contrast, they have lower contents of clay minerals, total organic carbon (TOC), free liquid hydrocarbons (S1), and total residual hydrocarbons (S2). The sand-silt intervals in the Yanchang shale serve as both pathways for hydrocarbon primary migration and “micro reservoirs” for hydrocarbon storage. The interconnected inorganic and organic pore systems, organic matter networks, fractures, and sand-silt intervals form the hydrocarbons’ primary migration pathways within the Yanchang shale. A model for the primary migration of hydrocarbons within the Yanchang shale is proposed.